P19 Audit of completion and documentation of neurovascular assessment prior to, and after Bier's block for distal radius fracture. (22nd July 2022) - Nwose, S; AkiiBua, A; Hussein, M
Abstract: Introduction: The BOAST guideline's standard of practise for the management of distal Radius Fractures states that assessment of circulation and sensation should be documented prior to and after MUA for distal radius fractures. We measured the compliance of the completion and documentation of the neurovascular assessment prior to and after Bier's Block for MUA of distal radius fractures. Methods: We assessed electronic medical records of these patients during the period November/December 2020. Focusing on the completion of the neurovascular assessment and documentation prior to Bier's Block and compared the results to our first cycle audit done in July/August 2020 following our intervention. Results: 58 patients were analysed for this study compared to 50 in the initial study. 88% had neurovascular assessment done and documented in the Emergency Department compared to 98% in the initial study. However, 60.3% had documentation of neurovascular assessment prior to Bier's block compared to 34% previously. 39.7% had vascular assessment after Bier's block and 64% had neurovascular assessment done in fracture clinic in this second cycle compared to 22% and 76% for vascular assessment and Neurovascular assessment in the facture clinic respectively after the MUA. Conclusion: This re- audit shows an improvement in the assessment and documentation of neurovascular Status prior to and following MUA of distal radius fracture. There is however a need for improvement. Suggested methods include teaching of upper limb neurological assessment to orthopaedic juniors, Aide memoire such as a small sticker to attach to the notes/ Stamp in the fracture clinic notes. Take-home message: Assessing and documenting neurovascular status before and after an MUA is very important.